Tuberculosis after commencing antiretroviral therapy for HIV infection is associated with elevated CXCL9 and CXCL10 responses to Mycobacterium tuberculosis antigens. - Oliver, B.; Elliott, J.; Price, Patricia; Phillips, M.; Cooper, D.; French, M. (Lippincott Williams & Wilkins, 2012)
Background: Commencing antiretroviral therapy (ART) in human immunodeficiency virus-infected patients with treated or unrecognized Mycobacterium tuberculosis disease may trigger tuberculosis-associated immune reconstitution inflammatory syndrome (TB-IRIS) or ART-associated tuberculosis (ART-TB). We have shown that whole-blood interferon-gamma release assays may aid in the prediction and diagnosis of ART-TB. Here, we investigate interferon-gamma-inducible chemokines CXCL9 and CXCL10. Methods: CXCL9 and CXCL10 responses to region of difference 1 (RD1) antigens and purified protein derivative (PPD) were assayed in plasma from whole-blood cultures collected before and after 4, 12, and 24 weeks of ART from 15 TB-IRIS cases, 11 ART-TB cases, and matched controls. Results: Relative to matched controls, ART-TB cases had elevated CXCL10 responses to RD1 antigens pre-ART (P = 0.02) and to PPD and RD1 antigens over 24 weeks of ART (P = 0.02 and P = 0.03). In contrast, TB-IRIS cases had higher CXCL10 responses to RD1 antigens before and after 4 weeks of ART only (P = 0.04 for both). CXCL9 responses to PPD and RD1 antigens were similar but less pronounced in ART-TB cases and did not differ between TB-IRIS cases and controls. CXCL10 responses to RD1 antigens performed as well as, or better than, IFN-γ responses in the prediction and diagnosis of ART-TB. Conclusions: Tuberculosis after commencing ART is associated with increased CXCL10 and, to a lesser extent, CXCL9 responses to M. tuberculosis antigens. Assessment of antigen-induced CXCL10 responses to RD1 antigens may assist in the prediction and diagnosis of ART-TB.